2015
DOI: 10.1016/j.phytochem.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Medicago spp. as potential sources of bioactive isoflavones: Characterization according to phylogenetic and phenologic factors

Abstract: A high variety of plant species are often proposed as potential natural sources of specific bioactive components, with emphasis in phenolic compounds. However, the ability to produce a determined phytochemical might be variable, even among species with close phylogeny. Furthermore, the metabolic dynamics vary greatly according to phenologic factors. Herein, it was verified whether isoflavone production in Medicago spp. is more associated with phylogenetic or phenologic determinants, to define the optimal produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
2
8
1
Order By: Relevance
“…Barreira et al [ 17 ] found that the average content of all isoflavones ranged from 1.25 to 3.16 mg·g −1 of DM in Medicago species, which was significantly higher than our measurements. The variance could be due to differences between the experiments.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Barreira et al [ 17 ] found that the average content of all isoflavones ranged from 1.25 to 3.16 mg·g −1 of DM in Medicago species, which was significantly higher than our measurements. The variance could be due to differences between the experiments.…”
Section: Discussioncontrasting
confidence: 89%
“…In recent years, phytoestrogens have been investigated by Wu et al [ 16 ], Lucas et al [ 5 ] and Barreira et al [ 17 ]. These works are primarily directed at evaluating such traditional legume species as red clover and alfalfa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Medicago genus belongs to the Leguminosae family and presents a wide range of interesting species for foods and feeds. These species are reported in many studies as sources of phytochemical compounds, including carotenoids, saponins, flavonoids and phytoestrogens [1][2][3] . These potential active ingredients have a significant preventive role against chronic diseases, especially when they are absorbed through the diet 4,5 .…”
Section: Influence Of Climate Variation On Phenolic Composition and Amentioning
confidence: 99%
“…Since the remaining co‐extracts after extraction did not negatively affect the resolution or the column life during the time of validation, the clean‐up step was not included. These authors have also developed MSPD‐based procedures for the extraction of isoflavones from different Medicago species (Barreira and others ; Visnevschi‐Necrasov and others ) and other plants belonging to the Leguminosae family (Cunha and others ), with the aim to evaluate isoflavone profiles. In this case C18 was used in a sorbent:to:sample ratio of 4:1 (w/w).…”
Section: Sample Preparationmentioning
confidence: 99%